2010
DOI: 10.1073/pnas.0914924107
|View full text |Cite
|
Sign up to set email alerts
|

FRET measurements of kinesin neck orientation reveal a structural basis for processivity and asymmetry

Abstract: As the smallest and simplest motor enzymes, kinesins have served as the prototype for understanding the relationship between protein structure and mechanochemical function of enzymes in this class. Conventional kinesin (kinesin-1) is a motor enzyme that transports cargo toward the plus end of microtubules by a processive, asymmetric hand-over-hand mechanism. The coiled-coil neck domain, which connects the two kinesin motor domains, contributes to kinesin processivity (the ability to take many steps in a row) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…In addition, the flexibility between the neck and stalk of kinesin-1 would endow the different orientations between them. The previous studies of kinesin-1 demonstrated that, during processive movement, the neck is parallel to the microtubule tracks, whereas the stalk seems somewhat more perpendicular to the tracks for holding cargoes (45). As for kinesin-3, NC forms the neck, whereas the CC1-FHA tandem may resemble the stalk of kinesin-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the flexibility between the neck and stalk of kinesin-1 would endow the different orientations between them. The previous studies of kinesin-1 demonstrated that, during processive movement, the neck is parallel to the microtubule tracks, whereas the stalk seems somewhat more perpendicular to the tracks for holding cargoes (45). As for kinesin-3, NC forms the neck, whereas the CC1-FHA tandem may resemble the stalk of kinesin-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular driving forces are integral components of diverse cellular processes, including transport of cargo along microtubules by kinesin, the separation of double-stranded nucleic acid structures, and the unfolding of substrate proteins prior to their degradation (Zolkiewski, 2006; Enemark and Joshua-Tor, 2008; Zhang et al, 2009; Martin et al, 2010; Myong and Ha, 2010). In each of these examples, molecular motors use the chemical energy of ATP hydrolysis to produce an asymmetrical conformational change, which is used to produce a mechanical force.…”
Section: Introductionmentioning
confidence: 99%
“…The surplus, naturally, goes into depots. Peters and Langemann, however, remained in doubt about this concept partly due to the fact that this “push” does not work invariably for all animal or human subjects (Martin et al, 2010; Cao et al, 2011). …”
Section: Push and Pull Parts Of Energy Supply Control Systemmentioning
confidence: 99%